Cerebrovascular dynamics after pediatric traumatic brain injury - Hanalioglu, Damla; Burrows, Brian T.; Adelson, P. David; Appavu, Brian (Frontiers in Physiology, 2023)
Objective: We aimed to investigate model-based indices of cerebrovascular dynamics after pediatric traumatic brain injury (TBI) using transcranial Doppler ultrasound (TCD) integrated into multimodality neurologic monitoring (MMM). Methods: We performed a retrospective analysis of pediatric TBI patients undergoing TCD integrated into MMM. Classic TCD characteristics included pulsatility indices and systolic, diastolic and mean flow velocities of the bilateral middle cerebral arteries. Model-based indices of cerebrovascular dynamics included the mean velocity index (Mx), compliance of the cerebrovascular bed (Ca), compliance of the cerebrospinal space (Ci), arterial time constant (TAU), critical closing pressure (CrCP) and diastolic closing margin (DCM). Classic TCD characteristics and model-based indices of cerebrovascular dynamics were investigated in relation to functional outcomes and intracranial pressure (ICP) using generalized estimating equations with repeated measures. Functional outcomes were assessed using the Glasgow Outcome Scale – Extended Pediatrics score (GOSE-Peds) at 12 months, post-injury. Results: Seventy-two separate TCD studies were performed on twenty-five pediatric TBI patients. We identified that reduced Ci (estimate -5.986, p=0.0309), increased CrCP (estimate 0.081, p<0.0001) and reduced DCM (estimate -0.057, p=0.0179) were associated with higher GOSE-Peds scores, suggestive of unfavorable outcome. We identified that increased CrCP (estimate 0.900, p<0.001) and reduced DCM (estimate -0.549, p<0.0001) were associated with increased ICP. Conclusion: In an exploratory analysis of pediatric TBI patients, increased CrCP and reduced DCM and Ci are associated with unfavorable outcomes, and increased ICP and reduced DCM are associated with increased ICP. Prospective work with larger cohorts is needed to further validate the clinical utility of these features.